EXPLORING UNDERGRADUATE EFL LEARNERS’ PSYCHOLOGICAL PROBLEMS IN WRITING AND COMPLETING THE THESIS - SITI NUR HAYATI; Ven. Dr. Penh Vibol; Edi Suwandi; SITI NUR HAYATI; Ven. Dr. Penh Vibol; Edi Suwandi (INTENS (International Journal of English Education and Linguistics), 2025)
Many students tend to procrastinate writing their thesis because they feel overwhelmed or don't know where to start. This phenomenon can be overcome by keeping a regular schedule, dividing tasks into smaller chunks, and setting realistic deadlines. feel worried that their thesis will not reach the expected standard. The purpose of this research is to analyze psychological factors that influence students in writing a thesis. Researchers used qualitative descriptions. This research method used questionnaires and interviews as instruments. Questionnaires are used to find detailed information on related factors that influence students in writing a thesis. The results of the psychological problem faced by undergraduate EFL learners show that English language education students have the highest score for the factors that affect writing thesis, namely from the results of the anxiety factor questionnaire shows the highest score gets 49.45% of students agree if they feel worried when comes to the advisor and the lowest inhibition factor gets 1.85% while for the motivation factor 2.5% of students have motivational support from both parent to quickly complete thesis, elf-esteem 2.5% of students agree if they have choose interesting title on writing a thesis, extroversion 2.35% the students was agree always optimistic about what they write in the thesis, empathy 12.18% the student agree the heart is easily touched when the friends and supervisor are giving salutation to the difficulty of writing thesis, risk taking 2.28% the students was will never lose, as long learn to win and improve the thesis. While the undergraduate EFL students overcome the problem of writing and completing a thesis is when meeting with your supervisor, focus on questions and solutions rather than feeling stressed or worried. If they are unsure about something, ask them honestly and open up.